Phosphate measurements from the neolithic settlement Wanna 1603, Ldkr. Cux., Germany - Moritz Mennenga; Pière Leon Frederiks (PANGAEA, 2023)
The samples examined were taken in the run-up to the sondage of a Neolithic settlement site under the bog near Wanna, district Cuxhaven, Germany. In order to determine the extent of the cultural layer, phosphate measurements were taken on the mineral sediment beneath the possible cultural layer. The measurements were carried out in the laboratory using an Agilent Cary 60 UV-Vis. The vanadate-molybdate method (Gericke and Kurmies 1952) was used to prepare the samples. The percentage is calculated according to the specification by = (β)*(measuring solution [4 ml]) / analyte [0.1 ml])*(total volume of digestion solution [1 ml] / conversion factor [1000])*(dilution factor [1])*(conversion factor weighed-in sample [1] /weighed-in sample pre ashed)*100.